Education at a glance 2012 : OECD indicators - (:unkn) unknown (OECD Publishing, 2012)
Education at a Glance "provides data on the structure, finances, and performance of education systems in the OECD's 34 member countries, as well as a number of non-member G20 nations. Featuring more than 140 charts, 230 tables, and 100 000 figures, 'Education at a Glance' provides key information on the ouput of educational institutions; the impact of learning across countries; the financial and human resources invested in education; access, participation and progression in education; and the learning environment and organisation of schools. In the 2012 edition, new indicators focus on: the effect of the global recession on education expenditures; the state of early childhood education systems around the world; intergenerational mobility in higher education among different socio-economic groups; the impact of education on macroeconomic outcomes, such as GDP; the specific factors that influence the level of education spending in different countries; [...]; the impact of examinations on access to secondary and higher education." (Verlag, BIBB-Doku)

Contents: Chapter A. The output of educational institutions and the impact of learning Chapter B. Financial and human resources invested in education Chapter C. Access to education, participation and progression Chapter D. The learning environment and organisation of schools
Keywords: S 1 Stufen der Berufsbildung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 4.1 Finanzierungsquellen; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; T 1.5 International vergleichende Berufsbildungsforschung; Bildungssystem; Effizienz; Indikatoren; Bildungsniveau; Bildungsökonomie; Bildungsertrag; Bildungsinvestition; Bildungsausgaben; Bildungsbeteiligung; Bildungsverlauf; Lernbedingungen; Bildungsstatistik; Quantitative Angaben; Internationaler Vergleich; OECD-Staaten